2012
DOI: 10.1111/j.1558-5646.2012.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Dynamics of Spite in Finite Populations

Abstract: Spite, the shady relative of altruism, involves paying a fitness cost to inflict a cost on some recipient. Here, we investigate a density dependent dynamic model for the evolution of spite in populations of changing size. We extend the model by introducing a dynamic carrying capacity. Our analysis shows that it is possible for unconditionally spiteful behavior to evolve without population structure in any finite population. In some circumstances spiteful behavior can contribute to its own stability by limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Similarly, creditors who engage in “coercive collection” by paying more in fees to collection agencies and attorneys than the value of the debt may be engaging in spiteful behavior (Leff, ). Because spiteful acts may benefit the non‐recipients of the act (e.g., the bacteria that survive the toxin now have access to more resources, the coercively collecting creditor helps enforce the prosocial norm that people should pay their debts), Smead and Forber () have dubbed spite “the shady relative of altruism” (p. 698). However, spite has also been linked to a variety of destructive behaviors including contentious custody battles during divorces that can harm parents' relationships with their children (Scott, ); persistent litigants and petitioners whose escalating complaints can result in legal, financial, and interpersonal losses to the complainant (Mullen & Lester, ); self‐injury by patients with borderline personality disorder as a way to punish people who care about the patient (Critchfield, Levy, Clarkin, & Kernberg, ); and at the extreme, spiteful suicides in which the act is partly committed to traumatize another (Joiner, ).…”
Section: Spitefulnessmentioning
confidence: 99%
“…Similarly, creditors who engage in “coercive collection” by paying more in fees to collection agencies and attorneys than the value of the debt may be engaging in spiteful behavior (Leff, ). Because spiteful acts may benefit the non‐recipients of the act (e.g., the bacteria that survive the toxin now have access to more resources, the coercively collecting creditor helps enforce the prosocial norm that people should pay their debts), Smead and Forber () have dubbed spite “the shady relative of altruism” (p. 698). However, spite has also been linked to a variety of destructive behaviors including contentious custody battles during divorces that can harm parents' relationships with their children (Scott, ); persistent litigants and petitioners whose escalating complaints can result in legal, financial, and interpersonal losses to the complainant (Mullen & Lester, ); self‐injury by patients with borderline personality disorder as a way to punish people who care about the patient (Critchfield, Levy, Clarkin, & Kernberg, ); and at the extreme, spiteful suicides in which the act is partly committed to traumatize another (Joiner, ).…”
Section: Spitefulnessmentioning
confidence: 99%
“…Territory contests are cases where aggressive behavior will be classified as selfish in some interactions, and spiteful in others. Furthermore, recent work on the evolutionary dynamics of social interactions reveals both interesting connections and important distinctions between various social behaviors (Lehmann et al 2006;West and Gardner 2010;Smead and Forber 2013). These observations suggest that classifying social behaviors will be more accurate and relevant if it is done in a way that captures such strategic features.…”
Section: The Standard and The Shiftmentioning
confidence: 93%
“…We showed that misclassification of indiscriminate harming is due to an implicit 274 assumption that the focal actor is a secondary recipient of its own behaviour (Hamilton 1970(Hamilton , 1971Grafen 1985;Vickery et al 2003;Taylor 2010;Smead & Forber 2012). This means that 276 some of the actor's direct benefit of harming has been accounted for by a fraction of the fitness effects on recipients, giving the appearance of an indirect benefit (RB > 0).…”
Section: Classifying Harming Traitsmentioning
confidence: 94%